Use of banana peel for the removal of copper (II) in aqueous solutions (Revista Científica Ciencias Naturales y Ambientales, 2024)
Currently, the presence of heavy metals in water constitutes a potential environmental concern,due to the harmful effects they can have on human health due to the level of toxicity theyhave. The raw material to obtain the bioadsorbent was banana peel (Musa paradisiaca); The unitoperations were applied, which consisted of: cleaning, drying, grinding and a characterizationof the bioadsorbent obtained. The determination of the FT-IR spectra, a bromatological andorganoleptic analysis were carried out: lignin, hemicellulose, color, odor and a physical-chemicalanalysis that included: humidity and ash as stipulated by the ASTM D5630-13 and ASTM D-4607standards. . The development of the adsorption tests was carried out through batch system tests,using four samples, an initial concentration of 0.93 mg/L, a pH of 5.4, and four contact times(45 min, 60 min, 120 min and 240 min), having the highest removal percentage in the M3 at120 min of 90.33%. In conclusion, the percentage of Cu (II) present in the solutions with Copper(II) sulfate pentahydrate was reduced using banana peel as a bioadsorbent and, above all, itwas demonstrated that agricultural waste such as banana peels can serve in water mitigation.contaminated and use of waste.
Keywords: Removal, bioadsorption, heavy metals, contamination; removal; bioadsorption; heavy metals; contamination